2019
DOI: 10.1371/journal.pone.0225071
|View full text |Cite
|
Sign up to set email alerts
|

Significant hearing loss in Fabry disease: Study of the Danish nationwide cohort prior to treatment

Abstract: BackgroundFabry disease (FD) is a lysosomal storage disorder resulting in systemic accumulation of globotriaosylceramide resulting in multi-organ dysfunction e.g. cerebral, cardiac, renal and audiologic complications. The audiologic involvement in FD has often been neglected; while not a lethal aspect of the disease, hearing loss can have a significantly negative impact on quality of life.ObjectivesTo investigate baseline hearing status of the Danish Fabry cohort prior to treatment, compared to sex- and age-ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 22 publications
0
8
1
Order By: Relevance
“…For the treated patients, baseline audiogram was defined as the most recent audiogram available prior to initiation of Fabry specific treatment. Due to limited data in the non-treated group, longitudinal analysis was only performed in the treated group which has in part been described before concerning other organ assessments [7] , [8] , [9] , [10] , [11] , [12] .
Fig.
…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the treated patients, baseline audiogram was defined as the most recent audiogram available prior to initiation of Fabry specific treatment. Due to limited data in the non-treated group, longitudinal analysis was only performed in the treated group which has in part been described before concerning other organ assessments [7] , [8] , [9] , [10] , [11] , [12] .
Fig.
…”
Section: Methodsmentioning
confidence: 99%
“…Previously, we presented the hearing status of the nationwide Danish Fabry cohort prior to treatment [7] . In the present study, we investigated the hearing through 16 years of follow-up of the Danish nationwide cohort.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 As adults, kidney dysfunction typically worsens, 11,14 and patients frequently suffer from stroke, 15 cardiovascular disease, 16,17 and hearing loss. 18,19 The decrease in lifespan experienced by Fabry patients is, in large part, caused by cardiac dysfunction and ischemic stroke. 20 Thrombotic events, including stroke and transient ischemic attacks, are a significant burden on patients and occur at a rate 7.1-and 3.1-fold higher than in the general public for male and female Fabry patients, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…During adolescence, additional symptoms frequently manifest, including gastrointestinal distress, 9,10 proteinuria, 11 and angiokeratomas 12,13 . As adults, kidney dysfunction typically worsens, 11,14 and patients frequently suffer from stroke, 15 cardiovascular disease, 16,17 and hearing loss 18,19 . The decrease in lifespan experienced by Fabry patients is, in large part, caused by cardiac dysfunction and ischemic stroke 20 .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies reported a markedly reduced quality of life (QoL) in FD patients, particularly in conjunction with pains [9], fatigue [10], depression [11], obstructive sleep apnea [12], hearing loss [13], and gastrointestinal symptoms [4]. In this relatively large patients group, we added data such as demographics, social status, clinical parameters, in addition to these manifestations.…”
Section: Introductionmentioning
confidence: 99%